Efficiency of AB Mix with Liquid Organic Fertilizer on Hydroponic Lettuce (Lactuca sativa L.) Growth - Dasumiati, Dasumiati; Fitri Mutiara Dewi,; Ardian Khairiah,; Junaidi,; Adeel Abdulkarim Fadhl Altuhaish, (Jurnal Biodjati, 2025)
The overuse of synthetic AB mix fertilizers in hydroponic systems raises concerns over chemical residues and long-term health risks. Incorporating liquid organic fertilizer (LOF) is a potential strategy to improve nutrient efficiency and enhance crop productivity. This study aimed to evaluate the application of liquid organic fertilizer (LOF) as a sustainable strategy to reduce AB mix dependency while maintaining crop growth and productivity. The experiment was arranged in a Completely Randomized Design (CRD) with five treatments: P1 (100% AB mix/control), P2 (25% LOF + 75% AB mix), P3 (50% LOF + 50% AB mix), P4 (75% LOF + 25% AB mix), and P5 (100% LOF). Plant growth and yield parameters were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT). The combination of LOF and AB mix significantly affected (P<0.05) plant height, root fresh weight, leaf number, and shoot fresh weight, but had no significant effect (P>0.05) on root length. All combinations of LOF and AB mix, including the 100% AB mix treatment, yielded statistically similar results across all measured parameters. However, the treatment with 75% LOF + 25% AB mix tended to produce the highest values, enhanced flavor, and did not reduce shelf life, whereas the 100% LOF treatment resulted in the lowest performance. These findings highlight the potential of LOF to substantially reduce synthetic input in hydroponic lettuce production, supporting more sustainable and health-conscious cultivation practices.